Nutritional status and academic performance in students - Díaz Tarazona, Amelia Madeleine (2020)
Objective. To identify the relationship between nutritional status and academic performance of students from the School of Business Sciences of Universidad de Huanuco, 2017-2018. Methods. It is a cross-sectional study, with a quantitative approach. Population comprised of 612 students, sample comprised of 235 students, selected probabilistically and all of them belonging to the first semester. Instruments used were made up of a socio-demographic survey, internal records for the identification of averages for mathematics and language courses, and an anthropometry card was used to measure nutritional status. Pearson's r correlation test was used in inferential analysis. Ethical considerations were taken into account at all times. Results. It was evident that 35.4 % (84) of the students had malnutrition, 5.9 % (14) for nutritional deficit and 29.5 % (70) for excess. 64.6 % (153) had a normal nutritional state. 60.8 % (144) obtained a regular academic performance, 30.8% (73) a poor performance and 8.4 % (20) a good performance. Conclusion. Nutritional status is significantly related to the academic performance of students from first semester of the School of Business Sciences, 2017 - 2018, of Universidad de Huanuco.